Digital justice: A rapid evidence assessment of the use of mobile technology for offender behavioural change - Taylor, Helen (Probation journal, 2023)
The increasing availability and use of mobile technology have allowed for innovative solutions to address a range of issues, especially in relation to health behaviour change. Such technological advances have also created opportunities within the justice context and the past decade has seen the development and use of mobile technology in the criminal justice system. Yet, little systematic research exists in this area. This study begins to fill this gap, through a rapid evidence assessment of the use of technologies, especially mobile applications and text message reminders, which support behaviour change amongst people in the criminal justice system.